Escape from freedom in the digital culture (Journal of Philosophy Culture and Political Science, 2023)
The modern era of the Internet and origin of digital culture are mainly explained by its postmodern character, in particular its risomatic structure. Decentralized and heterogenic network structure allows many network connections and the number of users to appear around the world. This changes the nature of human interaction in relational system from "human-human” to "human-technology-human”. In this regard, the understanding of the place of human, his main condition for functioning and development - possession of freedom, obtain the special relevance. Having freedom allows a person to transform the world around him, to create in accordance with the tasks and goals set in front of him. The definition “freedom” in the Erich Fromm’s book “Escape from freedom” becomes relevant in the modern digital time. Modern culture forms the valuable guidelines of the Internet environment and allows a person to choose and determine life meanings in the digital space independently, however, due to the strengthening of information and communication flows in social patterns, it is increasingly immersed in a state of detachment from its own being. The paradox of the escape and possession of the freedom has been analysed by the eminent scientist and the answer is given, which is helpful for the current digital society.Key words: Digital culture, digital space, freedom, escape from freedom.